La incidencia de las expresiones artisticas en el desarrollo de la expresiòn corporal en los niños/as del inicial 2 de la Unidad Educativa “Ramòn Paèz” ubicado en la parroquia Eloy Alfaro, cantòn Latacunga, provincia de Cotopaxi durante el año lectivo 2014-2015 - Gallardo Villacís, Jimmy Steven (2015)
The childhood stage has its own characteristics that are related to the development of children from 3 to5 years; it constitutes the basis for the physical, psychological, social development where knowledge, skills are assimilated, although it forms abilities and qualities of integrity, which in the past were considered practicable only in older children. This research wanted to demonstrate the importance of good care to children in their first years of life because of this care will depend on the kind of adult who will be in the future. The pre-school centers give attention and stimulate the motor development of children, while they are under their responsibility and the quality of it. Beside parents of the Educative Unit at "Ramón Páez” they do not know how to care their children and how to stimulate motor development they want to know orientations, stimulation childhood, in order to foster the abilities of their children from their homes and create them a nice emotional environment. The results of the research allowed verify the purpose of the work referred to the need for physical expression for childhood motor development through artistic expression. The beneficiaries of this research were children, parents and teachers directly or indirectly with great satisfaction.